PERUBAHAN POLA PERILAKU RELIGIUS SANTRI ALUMNI MAN IC LOMBOK TIMUR - Muhammad Furqon; Syafruddin Syafruddin; Nursaptini Nursaptini; Su'ud Su'ud (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2024)
This study aims to determine changes in religious behavior patterns of alumni of Madrasah Aliyah Negeri Insan Cendekia Lombok Timur. This research is a qualitative research with a case study approach. The types of data used are primary data and secondary data. The subjects in this study were alumni of Madrasah Aliyah Negeri Insan Cendekia Lombok Timur who graduated in 2020. Informants in this study were parents of alumni who graduated in 2020, teachers alumni, neighbors or relatives who knew the alumni well, and alumni boarding friends. The data collection techniques used were interviews, observation, and documentation. The data analysis techniques used are 1). organizing data, 2). Reading and memoing, 3). describing, classifying, and interpreting data into codes and themes, 4). interpreting data, 5). presenting and visualizing data. The results of this study indicate that the pattern of changes in alumni religious behavior, namely: 1). cultural changes in worship behavior, 2). cultural changes in terms of covering the aurat, and 3). cultural changes in terms of dating. 4)Temporary Changes, and 5) Permanent Changes